(untitled) (Italian Review of Legal History, 2020)
A dossier from the Carolingian Tuscany allows us to know the long and complex judicial case of the priest Alpulo. Born from a simple affair between a priest and a nun, the trial then disturbed a king, a count, an imperial messenger, five bishops and a large number of of people including lay people and clergymen. The reasons for such an expenditure of judicial energies can be recognised in the design of the Lucca episcopate to increase its land endowment in the area. Reading the dossier, however, we can get a more precise idea of the real functioning of Carolingian justice. It seems that the intentions declared by the Carolingian rulers – ensuring a greater protection of people’s rights and pomoting a justice less exposed to the arrogance of the powerful – must be understood with more scepticism than we usually do. Moreover, the interest of legal historians for the long judicial process is also recalled by certain passages which show compliance with a procedural discipline that is not at all elementary.